2003
DOI: 10.1002/cncr.11291
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well being and quality of life in ovarian cancer survivors

Abstract: BACKGROUND This report offers a unique analysis of the psychological distress associated with ovarian cancer in a review of natural correspondence between ovarian cancer survivors and an ovarian cancer newsletter. METHODS A review of 21,806 letters, cards, and e‐mails reflecting correspondence from January 1994 to December 2000 between ovarian cancer survivors and the founding editor of Conversations!: The International Newsletter for those Fighting Ovarian Cancer was performed using ethnographic qualitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 15 publications
2
116
1
3
Order By: Relevance
“…Recent studies suggest that coping strategies are determinants of the cancer patients' quality of life (Ferrell et al, 2003;Butow et al, 2013;Price et al, 2013). Moreover, they are considered modifiable aspects of the patients' lives that contribute to various health and psychosocial related outcomes.…”
Section: Coping and Quality Of Life In Turkish Women Living With Ovarmentioning
confidence: 99%
“…Recent studies suggest that coping strategies are determinants of the cancer patients' quality of life (Ferrell et al, 2003;Butow et al, 2013;Price et al, 2013). Moreover, they are considered modifiable aspects of the patients' lives that contribute to various health and psychosocial related outcomes.…”
Section: Coping and Quality Of Life In Turkish Women Living With Ovarmentioning
confidence: 99%
“…93 A qualitative review of natural correspondence between survivors of ovarian cancer and an ovarian cancer newsletter found that these women were able to describe their cancer experience and its effects on their lives in both negative and positive terms and that they often demonstrated resourcefulness and creative problem solving by sharing coping and survival strategies. 94 Research also suggests that cancer experience may have a positive influence on lifestyle change among adult cancer survivors who, in one study, reported a positive influence of cancer on smoking and diet: 46% of smokers reported quitting smoking, and 47% of respondents reported changing their dietary habits. 95 Research on positive outcomes among cancer survivors suggests that many view their treatment as an event that led to reevaluation of their life priorities, greater appreciation of relationships, greater sensitivity to needs of others, posttraumatic growth related to perceived threat to life, improved coping ability, and greater overall life satisfaction.…”
Section: Group 3: Patients With Subsyndromal Symptoms and Existentialmentioning
confidence: 99%
“…However, as gynaecological cancers have different profiles, the psychological challenges associated with these various malignancies may differ (Rieger, Touyz and Wain, 1998). Published research evaluating ovarian cancer include mostly qualitative studies (Ferrell et al, 2002(Ferrell et al, , 2003aHowell et al, 2003) and quality-of-life studies (Guidozzi, 1993;Anderson, 1994;Kornblith et al, 1995;Ersek et al, 1997;Borduka-Bevers et al, 2000;Lakusta et al, 2001). These studies indicate that disruptions to quality of life may occur, which includes significant distress, impairment in physical, vocational, social, familial and sexual functioning.…”
mentioning
confidence: 99%